KUALITAS HUBUNGAN ATASAN BAWAHAN SEBAGAI MEDIATOR DALAM HUBUNGAN KEPEMIMPINAN TRANSFORMASIONAL DENGAN PERILAKU CITIZENSHIP DAN KINERJA PEGAWAI DMINISTRATIF UNIVERSITAS JAMBI - edward .; RTS. Ratnawati (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2013)
Â Â This research focuses on tranformational leaderhsip and its relevance with public organization.The purpose is to examine the role of mediaton on superior subordinate relationshion the context of transformational leadership,withcitizenship and employee performance.The result shows 1)transformational leadership influence significantnly on superio subordinate subordinate relationship,citizenship berhavior,and employee performance,2)superior subordinate relationship effect the citizenship behavior and employee performance.The most finding of this research is superiot subordinater relationship strongly mediates the relation of transformational relationship and citizenship behavior and the employee performan.Kewords:Kepemimpinan transformasional,hubungan atasan-bawahan,perilaku citizenship,kinerja,Survei,Universitas Jambi